Presymptomatic cortical thinning in familial Alzheimer disease: A longitudinal MRI study. (8th November 2016) - Weston, Philip S.J.; Nicholas, Jennifer M.; Lehmann, Manja; Ryan, Natalie S.; Liang, Yuying; Macpherson, Kirsty; Modat, Marc; Rossor, Martin N.; Schott, Jonathan M.; Ourselin, Sebastien; Fox, Nick C.
Abstract : Objective: To identify a cortical signature pattern of cortical thinning in familial Alzheimer disease (FAD) and assess its utility in detecting and tracking presymptomatic neurodegeneration. Methods: We recruited 43 FAD mutation carriers—36 PSEN1, 7 APP (20 symptomatic, 23 presymptomatic)—and 42 healthy controls to a longitudinal clinical and MRI study. T1-weighted MRI scans were acquired at baseline in all participants; 55 individuals (33 mutation carriers; 22 controls) had multiple (mean 2.9) follow-up scans approximately annually. Cortical thickness was measured using FreeSurfer. A cortical thinning signature was identified from symptomatic FAD participants. We then examined cortical thickness changes in this signature region in presymptomatic carriers and assessed associations with cognitive performance. Results: The cortical signature included 6 regions: entorhinal cortex, inferior parietal cortex, precuneus, superior parietal cortex, superior frontal cortex, and supramarginal gyrus. There were significant differences in mean cortical signature thickness between mutation carriers and controls 3 years before predicted symptom onset. The earliest significant difference in a single region, detectable 4 years preonset, was in the precuneus. Rate of change in cortical thickness became significantly different in the cortical signature at 5 years before predicted onset, and in the precuneus at 8 years preonset. Baseline mean signature thickness predicted rate of subsequent thinning and correlated with presymptomatic cognitive change. Conclusions: The FAD cortical signature appears to be similar to that described for sporadic AD. All component regions showed significant presymptomatic thinning. A composite signature may provide more robust results than a single region and have utility as an outcome measure in presymptomatic trials.